Toronto, Woodson County - Zarich, Zac (Kansas State University, The Chapman Center for Rural Studies, 2017)
This study examines the town of Toronto, in Toronto Township, Woodson County, Kansas. The town was founded in 1869, and because of its location, it was at a disadvantage in terms of growth when compared to towns surrounding it. The town’s population never exceeded 829 residents. I used maps, papers, articles, census data, and fieldwork to write this paper.
Zac Zarich, “Toronto, Woodson, County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/198.
Keywords: Toronto Township; Woodson County; Woodson; S.R. Kellogg; Civil War; William P. Dennis